فاعلية البرامج العلمية ةالتدريبية على مستوى اللياقة البدنية والمهارية لدى لاعبي كرة القدم للناشئين فئة أواسط 16-18 سنة - عبيد, عمار; شايب, الجيلالي (My University, 2020)
هدفت هذه الدراسة إلى التعرف على مدى فاعلية برنامج تدريبي مقترح على اللياقة البدنية والمهارية لدى ناشئ كره القدم تحت سن 19 سنه ولتحقيق ذلك قام الباحث بدراسة البرامج التدريبية المتبعة من طرف المدربين الذين يشرفون على تدريب هذه الفئة وبحكم أن اللاعب الناشئ لديه مميزات وخصائص تختلف عن لاعبين في صنف الأكابر كنا بصدد إجراء دراسة للتعرف على فاعليه البرنامج على اللياقة البدنية والمهارية لدى ناشئ كره القدم بمتابعه المتغيرات البدنية و المهارية مثل التحمل العام السرعة الانتقالية تحمل السرعة تحمل القوه الرشاقة والقوه الانفجارية إضافة إلى متغيرات في المهارة الأساسية في كره القدم وأقسامها الجري بالكرة ضرب الكرة بالقدم المراوغات مهاجمه وغيرها وكان الهدف من دراستنا هو حصر العناصر البدنية التي تخلق فارق بين مستويات اللاعبين في كره القدم عند فئة اقل من 19 سنة فلما كان من الأهمية بمكان بان يطلع الباحث على الحالة البدنية والمهارية من خلال الاستجواب المدربين في عينة البحث ومقارنتها مع البرنامج التدريبي Research Summary This study aimed to identify the effectiveness of a proposed training program on fitness and skill for a young footballer under the age of 19 years. To achieve this, the researcher studied the training programs used by coaches who supervise the training of this category and the fact that the emerging player has features and characteristics that differ from players In the major category, we were in the process of conducting a study to identify the effectiveness of the program on physical fitness and skill for a young football by following physical and skill variables such as general endurance, transition speed, bearing speed, agility and explosive power, in addition to variables in the basic skill in football and its divisions, running with the ball, hitting the ball With foot dodgers attacking and others. The aim of our study was to limit the physical elements that create a difference between the levels of players in football at a category less than 19 years, so when it was important for the researcher to be acquainted with the physical and skill condition through interrogating the trainers in the research sample and comparing them with the program The training that was developed by the researcher, after reaching the results of the study The researcher recommended several recommendations, the most important of which are: Conducting theoretical study, conducting an in-depth analysis of similar studies, and generalizing the training program for young coaches Mainstreaming the program to sporting clubs and societies to benefit from it in raising the level of physical fitness, developing the skill of emerging players, and the researcher recommended the need to build standards for physical and skill variables based on them in sports selection and building and evaluating training programs
MES2020-13
Keywords: برنامج تدريبي; اللياقة البدنية; المهارات; كره القدم